Remote Sensing of Hydro-Meteorology - Lee, Joo-Heon; Kim, Jong-Suk; Jung, Young Hun; Sur, Chanyang (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Flood/drought, risk management, and policy: decision-making under uncertainty. Hydrometeorological extremes and their impact on human-environment systems. Regional and nonstationary frequency analysis of extreme events. Detection and prediction of hydrometeorological extremes with observational and model-based approaches. Vulnerability and impact assessment for adaptation to climate change.